2019
DOI: 10.3390/ma12030526
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Reactive MgO on the Reaction Process of Geopolymer

Abstract: In order to compensate for the shrinkage of geopolymer pastes uniformly, reactive MgO powders are evenly dispersed in the geopolymer. The deformation performance, mechanical properties, microstructure and components of geopolymer pastes with reactive MgO are characterized. The effects of the content and the activity of MgO are discussed. The results indicate that the chemical shrinkage, autogenous shrinkage and drying shrinkage decrease with the addition of reactive MgO. MgO reacted with water, and fine Mg(OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…An earlier and more extensive heat development corresponded to higher fineness of the slag. Others indicated also that higher Na 2 O concentration could also increase the amount of the developed heat but it cannot be confirmed in the present studies [23,34]. An interesting difference was observed before the development of the main peak.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…An earlier and more extensive heat development corresponded to higher fineness of the slag. Others indicated also that higher Na 2 O concentration could also increase the amount of the developed heat but it cannot be confirmed in the present studies [23,34]. An interesting difference was observed before the development of the main peak.…”
Section: Resultscontrasting
confidence: 77%
“…The Kb value was calculated as K b = (CaO + MgO)/(SiO 2 + Al 2 O 3 ) and the HM as HM = (CaO + MgO + Al 2 O 3 )/SiO 2 ). The data included values for the three types of slag used in this study and 8 other slags used by others [23,30,40,41]. All slags were activated with liquid sodium silicate SS and had fineness values showed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in CaO content is indicated from the pH of the two fly ash samples, i.e., FA2 shows higher pH than FA1. Although the MgO content was quite high, the result from Li (Li et al 2019) suggested it could have beneficial effect in reducing the shrinkage.…”
Section: Fly Ash Compositionmentioning
confidence: 99%
“…The authors wish to revise the authorship and the affiliations, due to the fact that we did not get the permission of the project leader of the Guangdong Water Conservancy Science and Technology Innovation Project (2015-10) in this published paper [1]. The previous authorship and affiliations were shown below:…”
mentioning
confidence: 99%